Correction of F8 intron 1 inversion in hemophilia A patient-specific iPSCs by CRISPR/Cas9 mediated gene editing - Hu, Zhiqing; Wu, Yong; Xiao, Rou; Zhao, Junya; Chen, Yan; Wu, Lingqian; Zhou, Miaojin; Liang, Desheng (Frontiers in Genetics, 2023)
Introduction: Hemophilia A (HA) is the most common genetic bleeding disorder caused by mutations in the F8 gene encoding coagulation factor VIII (FVIII). As the second predominant pathogenic mutation in hemophilia A severe patients, F8 Intron one inversion (Inv1) completely splits the F8 gene into two parts and disrupts the F8 transcription, resulting in no FVIII protein production. The part which contains exon 2-exon 26 covers 98% of F8 coding region. Methods: We hypothesized that in situ genetic manipulation of F8 to add a promoter and exon one before the exon two could restore the F8 expression. The donor plasmid included human alpha 1-antitrypsin (hAAT) promoter, exon one and splicing donor site (SD) based on homology-mediated end joining (HMEJ) strategy was targeted addition in hemophilia A patient-derived induced pluripotent stem cell (HA-iPSCs) using CRISPR/Cas9. The iPSCs were differentiated into hepatocyte-like cells (HPLCs). Results: The hAAT promoter and exon one were targeted addition in HA-iPSCs with a high efficiency of 10.19% via HMEJ. The FVIII expression, secretion, and activity were detected in HPLCs derived from gene-targeted iPSCs. Discussion: Thus, we firstly rescued the 140 kb reversion mutation by gene addition of a 975 bp fragment in the HA-iPSCs with Inv1 mutation, providing a promising gene correction strategy for genetic disease with large sequence variants.